Preparation and characterization of gel polymer electrolyte based on PVA-K2CO3 - Abdulkadir, B.A. (Bellwether Publishing, Ltd., 2020)
In this study, electrolyte materials were synthesized by mixing a highly conducting salt (K2CO3) with the poly(vinyl alcohol) (PVA) in different proportions (from 10 to 50Â wt.). The synthesized electrolyte was characterized using Fourier transform infrared (FTIR) spectroscopy, field-emission scanning electron microscopy (FESEM), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), electrochemical impedance spectroscopy (EIS), and linear sweep voltammetry (LSV) for their functional groups, morphology, thermal stability, glass transition temperature (Tg), ionic conductivity, and potential window, respectively. Characterization results show that the complex formation between PVA and K2CO3 salt has been established by FTIR spectroscopic study, which indicates the detailed interaction between PVA and the salts in PVA-K2CO3 composites while the amorphous nature of the electrolyte after incorporation of the salts has been confirmed by FESEM analysis. Similarly, TGA and DSC analysis revealed that both decomposition temperature and Tg of the synthesized electrolytes decrease with the addition of K2CO3 due to the strong plasticizing effect of the salt. The results confirm that the electrolytes have sufficient thermal stability for supercapacitor operation, as well as an amorphous phase to effectively deliver high ionic conductivity. The highest ionic conductivity of 4.53Â ÃÂ 10â3Â S cmâ1 at 373Â K and potential window of 2.7Â V was exhibited by PK30 (30Â wt. K2CO3), which can be considered as high value for solid-state electrolytes which are superior to those electrolytes from PVA salts earlier reported. The results similarly show that the prepared electrolyte is temperature-dependent as conductivity increase with increase in temperature. Based on these properties, it can be imply that the PVA-K2CO3 gel polymer electrolyte (GPE) could be a promising electrolyte candidate for EDLC applications. The results indicate that the PVA-K2CO3 as a new electrolyte material has great potential in practical applications of portable energy-storage devices. Â© 2020 Taylor & Francis.